2022
DOI: 10.2147/ccid.s384419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wound Healing and Anti-Inflammatory Activity of Hydroalcoholic Leaf Extract of Clematis simensis Fresen (Ranunculaceae)

Abstract: Introduction:Clematis simensis is one of the most widely used medicinal plant for the treatment of wound traditionally. However, its claim was not scientifically tested, the current study therefore assessed the anti-inflammatory and wound healing properties of 80% methanol leaf extract of C. simensis. Methods: The dried and powdered leaf of C. simensis was macerated with 80% methanol. The topical ointment was then made in two concentrations (5% and 10% w/w), and two models, excision and incision, were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, CSCs treatment with chestnut leaf extract combined with paclitaxel showed more efficacy in reducing the viability of CSC when compared with paclitaxel alone; however, such combinatory treatment showed no significant effects on MCF-7 cells ( Woo et al, 2017 ). Also, solvent fractions of selected medicinal plants ( Vernonia leopoldi , Clematis simensis ) ( Tuasha et al, 2020 ), characterized by the presence of numerous phytochemicals, including flavonoids ( Teshome et al, 2022 ; Tuasha et al, 2022 ), showed a potent capacity to reduce ALDH + subpopulations of JIMT-1 cells, and/or reduce colony formation, and/or reduced migration, and/or inhibit TNF-α-induced NF-κB nuclear translocation ( Tuasha et al, 2020 ). Many other plant extracts show significant capacity to suppress CSCs in breast cancer models, for example, pomegranate extract targeting BCSCs and EMT ( Nallanthighal et al, 2017 ) or hexane extract of Garcinia quaesita fruits inducing apoptosis of BCSCs isolated from MDA-MB-231 cells ( Colamba Pathiranage et al, 2021 ) with the potential to increase the effectiveness of therapeutics.…”
Section: Current Research On Flavonoids Targeting Cscs With the Poten...mentioning
confidence: 99%
“…Therefore, CSCs treatment with chestnut leaf extract combined with paclitaxel showed more efficacy in reducing the viability of CSC when compared with paclitaxel alone; however, such combinatory treatment showed no significant effects on MCF-7 cells ( Woo et al, 2017 ). Also, solvent fractions of selected medicinal plants ( Vernonia leopoldi , Clematis simensis ) ( Tuasha et al, 2020 ), characterized by the presence of numerous phytochemicals, including flavonoids ( Teshome et al, 2022 ; Tuasha et al, 2022 ), showed a potent capacity to reduce ALDH + subpopulations of JIMT-1 cells, and/or reduce colony formation, and/or reduced migration, and/or inhibit TNF-α-induced NF-κB nuclear translocation ( Tuasha et al, 2020 ). Many other plant extracts show significant capacity to suppress CSCs in breast cancer models, for example, pomegranate extract targeting BCSCs and EMT ( Nallanthighal et al, 2017 ) or hexane extract of Garcinia quaesita fruits inducing apoptosis of BCSCs isolated from MDA-MB-231 cells ( Colamba Pathiranage et al, 2021 ) with the potential to increase the effectiveness of therapeutics.…”
Section: Current Research On Flavonoids Targeting Cscs With the Poten...mentioning
confidence: 99%
“…A preliminary phytochemical screening of the extracts of the stem bark [15], root [16] and leaves [17] revealed the presence of polyphenols, alkaloids, tannin cardiac glycosides, steroids, terpenoids, tannins, and flavonoids. However, no report on phytochemical investigation that leading to isolation of secondary metabolites of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the systematic classification of Clematis poses challenges owing to their intricate nature and extensive morphological variability 4 . Currently, most studies have focused on morphological, physiological, ecological, and pharmacological activities 7 – 9 , whereas there are few basic molecular studies on germplasm resource identification, genetic breeding, resource conservation, and phylogeny. Furthermore, the chloroplast (cp) genome data of Clematis previously tested were submitted directly without detailed analysis, thus limiting our overall understanding of their phylogeny and genome evolution.…”
Section: Introductionmentioning
confidence: 99%